Connective tissue mast cells store and release noradrenaline - Yusuke Otani; Soichiro Yoshikawa; Kei Nagao; Takehiro Tanaka; Shinichi Toyooka; Atsushi Fujimura (Journal of Physiological Sciences)
Abstract Mast cells are present in mucosal and connective tissues throughout the body. They synthesize and release a wide variety of bioactive molecules, such as histamine, proteases, and cytokines. In this study, we found that a population of connective tissue mast cells (CTMCs) stores and releases noradrenaline, originating from sympathetic nerves. Noradrenaline-storing cells, not neuronal fibers, were predominantly identified in the connective tissues of the skin, mammary gland, gastrointestinal tract, bronchus, thymus, and pancreas in wild-type mice but were absent in mast cell–deficient W-sash c-kit mutant Kit W−sh/W−sh mice. In vitro studies using bone marrow–derived mast cells revealed that extracellular noradrenaline was taken up but not synthesized. Upon ionomycin stimulation, noradrenaline was released. Electron microscopy analyses further suggested that noradrenaline is stored in and released from the secretory granules of mast cells. Finally, we found that noradrenaline-storing CTMCs express organic cation transporter 3 (Oct3), which is also known as an extraneuronal monoamine transporter, SLC22A3. Our findings indicate that mast cells may play a role in regulating noradrenaline concentration by storing and releasing it in somatic tissues.